Answer:1. y = 2x - 3
2. y= 2x + 3
3. y = -2x + 3
4. y = -2x - 3
Step-by-step explanation:
Answer:
x = 
Step-by-step explanation:
Given
-
=
← factor denominator
-
= 
[ x ≠ 0, x ≠ - 1 as these would make the terms undefined ]
Multiply through by x(x + 1)
4x² - 5(x + 1) = 4
4x² - 5x - 4 = 4 ( subtract 4 from both sides )
4x² - 5x - 9 = 0 ← in standard form
(x + 1)(4x - 9) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 1 = 0 ⇒ x = - 1
4x - 9 = 0 ⇒ 4x = 9 ⇒ x = 
However, x ≠ - 1 for reason given above, then
solution is x = 
Answer:
Step-by-step explanation:
i believe you just have to add the fractions together since the denominator are the same :)
So in total Hazel can produce
Liters of juice
Answer:
-12≥x
Step-by-step explanation:
-10≥2x+14
-24≥2x
-12≥x
Hello, sorry if this seems a bit odd, it’s a common method though. Hope you can understand this. Thanks